1996
DOI: 10.1143/jjap.35.2649
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Effects in Z-Scan Measurements

Abstract: We investigate the behavior of the Z-scan technique in the case where the phase of the electric field departs from a Gaussian due to the saturation of the optical nonlinearity. The usual Gaussian decomposition theoretical approach cannot describe experimental results obtained with well-characterized chromium-doped saturable absorbers: ruby and alexandrite. This aim can be accomplished by extending the theory based on the Hankel transformation of the electric field through the inclusion of the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 11 publications
2
12
0
2
Order By: Relevance
“…The importance of proper consideration of saturation has been considered by several authors 18 and can be seen in Fig. 7.…”
Section: B Z-scan Measurementsmentioning
confidence: 99%
“…The importance of proper consideration of saturation has been considered by several authors 18 and can be seen in Fig. 7.…”
Section: B Z-scan Measurementsmentioning
confidence: 99%
“…The first quantitative measurement of the nonlinearity in ruby was made using an interferometric technique [10] that conclusively demonstrated the dispersive origin of the phase conjugation, since it was measured that the real part of the refractive index change was 1 order of magnitude larger than the imaginary one. From this result, it was found that the polarizability difference between excited and ground states of ruby is Δα p 1.6 × 10 −25 cm 3 , a value which was later confirmed by several experiments [4,7,[11][12][13][14][15]. For instance, the dispersive character of ruby's nonlinearity was demonstrated with the nondegenerate two-wave mixing (NDTWM) experiments of McMichael et al [11].…”
Section: Introductionmentioning
confidence: 67%
“…The experimental setup is similar to the classical Z-scan one [35], with the introduction of a chopper in order to allow time-resolved detection to eliminate parasitic linear effects [13,38]. As explained before, the refractive index change in Cr 3 -doped crystals originates from the metastable excited state, which has a polarizability different from that of the ground state.…”
Section: Z-scan Measurementsmentioning
confidence: 99%
“…It shows a departure from the expected asymmetric shape [9] because saturations effects distort the lens induced by nonlinear processes. In order to treat this situation in a rigorous way, the Hankel transformation method should be employed to deal with the light propagation in the case where the induced phase is not Gaussian [14]. This cumbersome analysis is out of the scope of the present work.…”
Section: Resultsmentioning
confidence: 99%